Straw cellulose obtaining in the isobutanol - hydrazine – KOH system - Барбаш, Валерій Анатолійович; Ященко, Ольга Василівна (Technology audit and production reserves, 2014)
The delignification process of wheat straw in isobutyl alcohol - hydrazine – KOH system in the range of 140-160 0C and length 60-150 min is investigated. It is shown that the quality values of obtained cellulose are naturally decreased with increasing of temperature and duration of cooking, due to the intensification of lignin destruction process. Laboratory castings of straw pulp has the following physical and mechanical properties, tensile length of 6200-6900 meters, forcing index 4,2-4,5 kN/g, number of double kinks 520-600, that is higher than the wood cellulose quality obtained by traditional sulfate and sulfite cooking methods. The chemical composition of top layer of worked-out solution is determined by the method of proton magnetic resonance. Four major peaks that correspond to isobutanol groups and confirm ability to use the top layer of worked-out cooking solution to the following cooking are observed in the obtained spectra.